Chemical Composition and Aroma Profiling: Decision Tree Modeling of Formalin Tofu - Huzain Azis; Sitti Rahmah Jabir (Journal of Embedded Systems, Security and Intelligent Systems, 2023)
This study focuses on the analysis of the aroma quality of tofu preserved with formalin, with the goal of developing a predictive model based on its chemical composition. Utilizing a dataset that includes various chemical components such as Hydrogen, LPG, CO, Alcohol, Propane, Methane, Smoke, and temperature, this research applies a Decision Tree model. The model is validated using 5-fold cross-validation, resulting in an accuracy of 36.79%, precision of 50.82%, recall of 36.79%, and an F1-Score of 27.58%. These results indicate the model's limitations in consistent prediction, suggesting potential improvements through other methods or the addition of variables. This study provides new insights into the relationship between chemical composition and aroma quality of formalin tofu, and opens new avenues for further research in this field.